Pathology of gastrointestinal disorders of rabbits - Devi S S (Centre for Excellence in Pathology, College of Veterinary and Animal Sciences, 2007)
The present study was undertaken to assess the prevalence and pathology of gastrointestinal disorders in rabbits. The results of the study revealed a high incidence of gastrointestinal disorders in rabbits. The study was based on a detailed postmortem examination of fifty rabbit carcasses. The gross and histopathological lesions were closely observed and classified based on age and nature of changes. Vascular lesions were predominant in the stomach whereas inflammatory conditions outnumbered vascular and degenerative changes in the intestine. In the stomach the most conspicuous vascular change was congestion while catarrhal gastritis was the prominent inflammatory lesion. Catarrhal enteritis was the commonly observed pathology in the intestine. Parasitic as well as bacterial agents were found to be associated with the lesions. The most important bacterial pathogens isolated were E. coli and Salmonella. Intestinal coccidiosis was also observed in a considerable number of cases. Various developing forms of Eimeria spps were identified in the sections of duodenum and jejunum in affected cases. Verminous enteritis was observed in one case where the larvae of pinworm was seen penetrating the submucosa of the jejunum. Mesenteric lymph nodes of fifteen cases revealed vascular, degenerative and necrotic changes of varying degrees. Depletion of lymphocytes associated with degeneration and necrosis of germinal centers in lymphoid follicles of mesenteric lymph nodes were all indicative of immune suppression. Lymphoid depletion was also evident in the Peyer’s Patches of ileum. Liver samples of thirty animals showed pathological changes, some in combination with gastrointestinal lesions. Pasteurella was isolated from the liver in two cases with hemorrhagic tracheitis. Hepatic coccidiosis was observed in certain cases, which were histologically characterized by bile duct hyperplasia, fatty degeneration and vascular changes. The higher incidence of gastrointestinal disorders, the role of immune suppression and isolation of different pathogens indicated the necessity for an indepth study on the multi factorial etiology associated with gastrointestinal disorders in rabbits.